Preface: Hydrological processes and water security in a changing world - Yu, Zhongbo; Lu, Chunhui; Cai, Jianyuan; Yu, Dazheng; Mahe, Gil; Mishra, Anil; Cudennec, Christophe; Van Lanen, Henny A. J.; Orange, Didier; Amani, Abou (Proceedings of the International Association of Hydrological Sciences, 2020)
[...]understanding hydrological responses to stresses at local, regional and global scales is critical for addressing these water issues, including water resources planning and management for everywhere on the planet. The 8th Global FRIEND conference was co-organized by UNESCO and Government of China from 6–9 November 2018 in Beijing, with the focus on the theme of hydrological processes and water security in a changing world, under which eight thematic topics were discussed during the conference: (1) hydrological observations under the changing environment and scarcity; (2) river regimes and hydrological extremes under the changing environment; (3) simulation and prediction of surface water and groundwater processes under the impact of human activities; (4) urban hydrology and sponge city; (5) multi-objective water resources allocation and operation; (6) integrated watershed management including eco-hydrology and socio-hydrology; (7) water quality and sediment transport; and (8) river health and ecological baseflow under changing environment. Furthermore, the outcome of the conference presented in the proceedings will be shared and discussed widely among IHP networks which would lead to recommend inputs for sustainable water resources management at different scale, but also provide feedbacks for the preparation of strategic plan for the ninth phase of IHP (IHP IX, 2022–2029).